Conceitualização na construção de ontologias: relações semânticas no âmbito do Blood Project - Livia Marangon Duffles Teixeira (2009)
The ontology research has been received much attention because of the several oportunities that it offers in the information organization aiming to be used both by people or by machines. The most important phase In the ontology development process is called conceptualization, thus it should receive special attention because of its importance and complexity. This work aims to obtain improvements in the Conceptualization stage, using Linguistic approaches, namely troponimy and frame semantics, to check variations in the semantic of relations. We present a case study in the domain of medicine, which is part of Blood Project, and offer our conclusions about the variety of possibilities to define semantic relations in extracting verbs and adverbs from medical texts.